Towards the enhancement of Arctic digital industries: 'Translating'cultural content to new media platforms - Pasch, Timothy (The Journal of Specialised Translation, 2015)
This paper proposes a preliminary framework for digital 'translation' attempting to, (while cognisant of conceptual limitations embedded in this model) localise aspects of Inuit knowledge, culture and IQ (in the sense of Inuit Qaujimajatuqangit) into digital artifacts for new generations of Inuit and non-Inuit learners. In addition to delineating challenges and opportunities based on theoretical models and actual projects currently underway in Nunavut and Nunavik, it proposes developing Arctic digital industries through convergent cultural media. Finally, it encourages US and Canadian governments during this four-year North American governance cycle of the Arctic Council (two years each for Canada (2013-2015) and the United States (2015-2017) to invest in digital infrastructure, from both a humanistic (via training) and technological perspective. Conceptually, the article argues that culturally focused circumpolar digital development is fundamental to fulfilling the language of the Canadian and US Arctic Strategies, indicating the importance of validating the cultures and voices of the 'People of the North'. It warns against potential post-colonial dangers inherent in digital training, and concludes by arguing that based on current increased global focus on the resources and geo-strategic possibilities inherent in the Arctic (accelerated by global warming and augmented militarisation of the North), that the time is pivotal to ensure that digitally localised and disseminated voices of the Inuit and circumpolar indigenous voices are available electronically in the widest possible variety of media forms.